"Superfast!" managing the urgent: case study of telecommunications infrastructure project in Algeria. Issue 2 (16th April 2018) - Zidane, Youcef J-T.; Klakegg, Ole Jonny; Andersen, Bjorn; Hussein, Bassam
Abstract : Purpose: With the aim of furthering the understanding of project speed and how to manage the urgent project, the purpose of this paper is to investigate the management challenges involved in delivering a telecommunications infrastructure project in a period of much shorter duration than a similar project. The authors wanted to understand the reasons behind the urgency and how the project management team succeeds in delivering in such a tight time window. Finally, the authors assessed the consequences (negative and positive, during and after the project delivery), knowing that the project was considered a success at its delivery, but not that it was successful at the post-project evaluation. Design/methodology/approach: A case study based on qualitative research interviews with management team including the client, the main contractor and some related stakeholders, combined with case archives and internal documentation from the case project. Findings: The urgency of a project or programme may lead to some negative consequences and impacts. The success seen in a short- and mid-term view is not enough to justify making acceleration decisions: thus holistic thinking and a long-term sustainable approach are needed to ensure continuity and profits. Research limitations/implications: This research is based on a single case study. There are some limitations regarding how urgent and unexpected the case was managed in comparing to normal case. A second limitation is that there is no clear definition of what are normal practices such that we can say what are a normal case and an urgent case. Practical implications: There are some lessons learned from this case study about managing the unexpected and the urgent. Practitioners can obtain insight into positive and negative consequences of fast project delivery from this case. Originality/value: This study is unique in its content and context, since it presents the first-hand insight into a case study that seemed to be successful to some extent (short-term impact); however, negative consequences appeared within a few years of its delivery.